Local prevalence of extended-spectrum beta-lactamase (ESBL) producing Enterobacteriaceae intestinal carriers at admission and co-expression of ESBL and OXA-48 carbapenemase in Klebsiella pneumoniae: a prevalence survey in a Spanish University Hospital - Díaz-Agero Pérez, Cristina (BMJ Open, 2019)
OBJECTIVE: To assess the prevalence of extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae (ESBL-E) faecal carriers at admission in a University Hospital in Spain. DESIGN: Prevalence survey. SETTING: Pneumology, gastroenterology, urology and neurosurgery units at a university tertiary hospital in Madrid (Spain). PARTICIPANTS: A total of 10 643 patients aged 18 and older admitted from March 2014 to April 2016 with a rectal swab taken at admission or as soon as possible within the first 48 hours. PRIMARY AND SECONDARY OUTCOME MEASURES: Prevalence of ESBL-E faecal carriers and prevalence of ESBL-E infections at admission. RESULTS: The prevalance of ESBL-E carriers at admission was 7.69% (CI 95% 7.18 to 8.19). Most of the isolates were Escherichia coli (77.51%), followed by Klebsiella pneumoniae (20.71%). Eighty-eight (10.41%) of ESBL-E were simultaneous ESBL and carbapenemase (CP) producers, 1.83% in the case of E. coli and 42.86% among K. pneumoniae isolates. Of the ESBL typed, 52.15% belonged to the cefotaximases (CTX-M-15) type and 91.38% of the CP were oxacillinase (OXA-48) type. Only 0.43% patients presented an active infection by ESBL-E at admission. CONCLUSIONS: The prevalence found in our study is very similar to that found in literature. However, we found a high percentage of simultaneous ESBL and CP producers, particularly in K. pneumoniae. Despite the high prevalence of colonised patients, the ESBL-infection rate at admission was very low.